Antimicrobial evaluation and molecular properties prediction of pyrazolines incorporating benzofuran and pyrazole moieties - Mervat A. Elsherif&, Ashraf S. Hassan, Gaber O. Moustafa, Hassan M. Awad, Nesrin M. Morsy (Journal of Applied Pharmaceutical Science, 2020)
A series of chalcones 3–5, 1H-pyrazolines 6–8, N-phenylpyrazolines 9–11, and N-acetylpyrazolines 12–14 incorporating benzofuran and pyrazole moieties were synthesized and screened for their in vitro antimicrobial activity against some of pathogenic microorganisms. Among the screened compounds, 7 and 13 showed the most promising antibacterial activity against Escherichia coli (G-). Compound 11 displayed broad spectrum antibacterial activity against Bacillus subtilis (G+). Moreover, compounds 10 and 4 were found to be the most potent antifungal agent against Candida albicans and Aspergillus niger, respectively. Also, the molecular properties prediction and drug-likeness model score (DLS) of all the synthesized compounds were calculated by SwissADME and MolSoft websites, respectively. The two compounds 7 and 13 were found to be maximum DLS of 0.75 and 0.83, respectively.
Keywords: Pyrazoline, benzofuran, pyrazole, antimicrobial activities, drug-likeness, Lipinski rules.